The Sleep Condition Indicator: a clinical screening tool to evaluate insomnia disorder. Issue 3 (18th March 2014) - Espie, Colin A; Kyle, Simon D; Hames, Peter; Gardani, Maria; Fleming, Leanne; Cape, John
Abstract : Objective: Describe the development and psychometric validation of a brief scale (the Sleep Condition Indicator (SCI)) to evaluate insomnia disorder in everyday clinical practice. Design: The SCI was evaluated across five study samples. Content validity, internal consistency and concurrent validity were investigated. Participants: 30 941 individuals (71% female) completed the SCI along with other descriptive demographic and clinical information. Setting: Data acquired on dedicated websites. Results: The eight-item SCI (concerns about getting to sleep, remaining asleep, sleep quality, daytime personal functioning, daytime performance, duration of sleep problem, nights per week having a sleep problem and extent troubled by poor sleep) had robust internal consistency (α≥0.86) and showed convergent validity with the Pittsburgh Sleep Quality Index and Insomnia Severity Index. A two-item short-form (SCI-02: nights per week having a sleep problem, extent troubled by poor sleep), derived using linear regression modelling, correlated strongly with the SCI total score (r=0.90). Conclusions: The SCI has potential as a clinical screening tool for appraising insomnia symptoms against Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria.